The provided recursive function can be analyzed as follows:
- When
n
is 1, the function returns 3. - For any other value of
n
, the function calls itself withn - 1
and adds 3 to the result.
This means that the function calculates:
- For
n = 1
:mystery(1) = 3
- For
n = 2
:mystery(2) = mystery(1) + 3 = 3 + 3 = 6
- For
n = 3
:mystery(3) = mystery(2) + 3 = 6 + 3 = 9
- For
n = 4
:mystery(4) = mystery(3) + 3 = 9 + 3 = 12
- And so on...
We can see that for n
, the function returns \(3 + 3(n - 1)\). This is because each reduction in n
adds 3, effectively making it \(3 \times n\).
Thus, the mathematical function defined by this recursive function is:
3 times n (or mathematically represented as \(3n\)).